Continuous-wave Nd:GYSGG laser at 1.1 μm. Issue 4 (23rd February 2018) - Lin, Hongyi; Liu, Hong; Huang, Xiaohua; Copner, Nigel; Sun, Dong
Abstract: We demonstrated a compact and simple continuous-wave (CW) Nd:GYSGG laser with triple-wavelength lines at 1105, 1107 and 1110 nm based on R2 → Y6, R1 → Y5 and R1 → Y6 of the 4 F3/2 → 4 I11/2 transition. The total output power of the triple-wavelength lines was 480 mW. Moreover, we obtained an efficient CW Nd:GYSGG laser at 1110 nm with the output power of 1560 mW at the pump power of 11.05 W. Those lines at 1058 and 1062 nm were suppressed completely by the simple output mirror of high transmission at 1.06 μm.